New records of coastal tropical fish in Peru - Hooker, Yuri (2009)
In this paper I report on 11 new records of marine fishes from Peru. The collections were made between 1989 and 2007 in Bocapan, Canoas de Punta Sal, Punta Sal (Tumbes); Los Órganos, Isla Foca (Piura); Islas Lobos de Afuera (Lambayeque); Bahía Samanco (Ancash); y Pucusana (Lima). The new records for the marine fish fauna of Peru are: Dasyatis longa, Urobatis halleri, Cephalopholis panamensis, Prognathodes carlhubbsi, Cirrhitus rivulatus, Stegastes beebei, Thalassoma lucasanum, Thalassoma grammaticum, Axoclinus lucillae, Elacatinus punticulatus and Coryphopterus urospilus. Cirrhitichthys oxycephalus, Lythrypnus dalli and Myripristis leiognathus, previously have been referred to Peru but not documented there, this paper certify their presence.